An Improving Public Trust: Renakta Police Investigators' Complaint Handling Model in South Sumatra's Criminal Investigations - Saputra, Ade Candra; Azhar, Azhar; Putra, Raniasa (PERSPEKTIF, 2024)
Handling public complaints is important in public services in Indonesia, including in the field of law enforcement by the Indonesian National Police (Polri). National Police investigators have a crucial role in conducting investigations and investigations into criminal acts involving juveniles, children, and women. However, there are challenges in ensuring the effectiveness of complaint handling to increase public trust. This study aims to investigate the practice of handling complaints by investigators of the Sub-Directorate of the Ditreskrimum of the South Sumatra Regional Police, especially related to cases involving vulnerable groups. The research method used is qualitative with in-depth interviews with investigators and related parties. The results highlight supporting and inhibiting factors in handling complaints and formulate a complaint-handling model that can be applied by investigators to increase public trust. Thus, applying this model is expected to build a fair, responsive environment, and increase public confidence in law enforcement agencies in handling cases involving vulnerable groups.